Comorbidities and Age Are Associated With Persistent COVID-19 PCR Positivity - Aldhaeefi, Mohammed; Tahir, Zabreen; Cote, David J.; Izzy, Saef; El Khoury, Joseph (Frontiers in Cellular and Infection Microbiology, 2021)
Objectives: The impact of demographics and comorbidities on the duration of COVID-19 nasopharyngeal swab PCR positivity remains unclear. The objective of our analysis is to determine the impact of age, intensive care unit (ICU) admission, comorbidities, and ethnicity on the duration of COVID-19 PCR positivity among hospitalized patients in a large group of hospital Method: We studied 530 patients from a large hospital system and time to SARS-CoV-2 virus RNA PCR negativity at any-time during hospitalization or following discharge from the hospital was the primary endpoint. We included patients 18 years or older who tested positive for COVID-19 during an inpatient, outpatient, or emergency room visit between February 1, 2020, and April 14, 2020 Results: Overall, 315 (59.4%) of our patient population continued to have a positive SARS-CoV-2 virus RNA PCR 4 weeks after the initial positive test. We found that age>70 years, chronic kidney disease, hypertension, hyperlipidemia, obesity, or coronary artery disease are associated with persistent PCR positivity for more than 4 weeks after initial diagnosis. Conclusion: Age, and the presence of co-morbidities should be taken into consideration when interpreting a positive COVID PCR test